Waste Plastic Thermal Pyrolysis: A Recent Advanced Study - Yansaneh, Osman Y.; Zein , Sharif H. (Current Overview on Science and Technology Research Vol. 1, 2022)
This work is essentially a simplification of a collection of thermal pyrolysis research work, mostly recent, being reviewed and referenced here, and showcasing the increased interest in pyrolysis treatment methods. The management of waste plastic (WP), also known as post-consumer plastic (PCP), poses a significant difficulty in the modern world due to its distinctive biodegradation characteristics. With an increase in demand for plastic use, waste plastic production also rises in line. According to research, this desire rises yearly. Most of these waste plastics include high- density polyethylene (HDPE), low-density polyethylene (LDPE), polyethylene terephthalate (PET) and polystyrene (PS). These wastes may be rich in resources, and research has shown that pyrolysis is a reliable method for realising this potential. A thorough analysis of waste plastics thermal pyrolysis (WPTP) is conducted in this critical evaluation. The yield and selectivity of the product are discussed, and a WPTP comparative quality guarantee is looked at. This report provides assurance into the most recent WPTP findings and identifies several gaps and misunderstandings that are frequent in this area and should be addressed in order to enable future research. Additionally, the importance of co-pyrolysing plastic waste with biomass is emphasised, and the impact of mixed waste plastics on pyrolysis is shown.